2023
DOI: 10.3390/metabo13070786
|View full text |Cite
|
Sign up to set email alerts
|

Protective Action Mechanisms of Launaea mucronata Extract and Its Nano-Formulation against Nephrotoxicity in Rats as Revealed via Biochemical, Histopathological, and UPLC-QTOF–MS/MS Analyses

Abstract: Plants belonging to the Launaea genus have been extensively utilized ethnopharmacologically to treat a variety of diseases, including kidney disorders. Chromium is a common industrial pollutant that has been linked to kidney disease. The present work was designed for the investigation of the UPLC-QTOF–MS/MS metabolite profile of the L. mucronate ethanolic extract (LME), along with assessing the mechanistic protective actions of LME and its nano-silver formulation (LMNS) against K2Cr2O7-induced nephrotoxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Swiss albino mice were administered gradient oral doses of CCEO, up to 2000 mg/kg bw, without any observable signs of toxicity or mortality within 24 h. From these observations, it can be concluded that the median lethal dose (LD50) of CCEO in mice is expected to be higher than 2000 mg/kg. According to classification criteria, as reported in previous literature, substances with LD50 values exceeding 50 mg/kg body weight are generally considered to be non-toxic [ 13 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swiss albino mice were administered gradient oral doses of CCEO, up to 2000 mg/kg bw, without any observable signs of toxicity or mortality within 24 h. From these observations, it can be concluded that the median lethal dose (LD50) of CCEO in mice is expected to be higher than 2000 mg/kg. According to classification criteria, as reported in previous literature, substances with LD50 values exceeding 50 mg/kg body weight are generally considered to be non-toxic [ 13 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lungs were washed with saline and placed in ice-cold phosphate buffer (pH 7.4) to prepare 20% homogenate using a homogenizer (Heidolph, DIAX 900, Burladingen, Germany). The homogenates were centrifuged at 2000× g for 20 min at 4 • C. The supernatant was collected and stored at −80 • C [13] and then used for estimation of lung contents of TNF-α and TGF-β using NOVA (Beijing, China) ELISA kits and of IP3k using SunRed Biotechnology Company ELISA kits. Another part of lung tissue was kept in 10% formalin-saline for histopathological examination.…”
Section: Biochemical Determinationmentioning
confidence: 99%
“…The macerated plant with ethanol was filtered using a Buchner funnel lined with gauze between small pieces of cotton; the beaker was attached with a vacuum pump to facilitate the filtration process; the filtrate of N. sativa was dried using a rotary evaporator at 40 • C (Heidolph, Schwabach, Germany). The evaporated extract (75 g) was collected and kept in the refrigerator until it was used for phytochemical analysis and biological assays [46].…”
Section: Extraction Processesmentioning
confidence: 99%